TECHNICAL IMMERSION ON LEARNING BASIC LIGHTING IN VIRTUAL REALITY FILM CAHAYA CINTA PERLAHAN MENYILAUKAN - Rinto, Frans Sahala Moshes (Institut Seni Budaya Indonesia Bandung, 2023)
ABSTRACT The film Cahaya Cinta Perlahan Menyilaukan was developed as an alternative way of learning vocational skills, especially in a film production environment. The purpose of this research was to find how the technical immersion which includes visual cues, audio cues, orientation cues, and disorientation cues associated with the competencies in SKKNI No. 154/2020 for national competence of film lighting operator, including key functions, main functions, and basic functions in the delivery of lighting learning materials through virtual reality media which is also a contemporary media that is currently widely used. Immersion in practice itself is an attempt to involve the audience so that they can go in depth and be able to absorb. This film has two episodes and three different interactive levels in order to learn the basics of film lighting. The research uses qualitative characteristics which are applied through analysis of the technical immersion. The material of interactivity, visual and audio show that technical immersion provides direction in learning and attracts the attention of the audience without reduce the substance of the learning content based on competencies in SKKNI No. 154/2020. ABSTRAK Film Cahaya Cinta Perlahan Menyilaukan dikembangkan sebagai salah satu cara alternatif pembelajaran keterampilan kejuruan, khususnya dilingkup produksi film. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana teknik perendaman yang meliputi isyarat visual, isyarat audio, isyarat orientasi, dan isyarat disorientasi dikaitkan dengan kompetensi dalam SKKNI No. 154/2020 untuk kompetensi nasional operator lighting film, meliputi fungsi pokok, utama fungsi, dan fungsi dasar dalam penyampaian materi pembelajaran pencahayaan melalui media virtual reality yang juga merupakan media kekinian yang saat ini banyak digunakan. Immersion dalam praktek sendiri merupakan upaya untuk melibatkan penonton agar dapat mendalami dan mampu menyerap. Film ini memiliki dua episode dan tiga level interaktif berbeda untuk mempelajari dasar-dasar pencahayaan film. Penelitian ini menggunakan karakteristik kualitatif yang diterapkan melalui analisis teknis imersif. Materi interaktivitas, visual dan audio menunjukkan bahwa teknis imersif memberikan arahan dalam pembelajaran dan menarik perhatian penonton tanpa mengurangi substansi isi pembelajaran berdasarkan kompetensi pada SKKNI No.154/2020.